Proceedings of the Workshop on Cognitive Modeling and Computational Linguistics 2019
DOI: 10.18653/v1/w19-2903
|View full text |Cite
|
Sign up to set email alerts
|

Simulating

Abstract: Multilingual speakers are able to switch from one language to the other ("code-switch") between or within sentences. Because the underlying cognitive mechanisms are not well understood, in this study we use computational cognitive modeling to shed light on the process of code-switching. We employed the Bilingual Dual-path model, a Recurrent Neural Network of bilingual sentence production (Tsoukala et al., 2017) and simulated sentence production in simultaneous Spanish-English bilinguals. Our first goal was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…This confirmed that the error may be caused by a transfer effect from Spanish pro-drop. The Spanish-English bilingual Dual-Path model can also produce code-switched sentences, even though it was never exposed to code switches during training (Tsoukala, Frank, Van den Bosch, Valdés Kroff, & Broersma, 2019). The patterns of generated code switches show some resemblance to those of Spanish-English bilinguals.…”
Section: Bilingual Rnn Sentence Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…This confirmed that the error may be caused by a transfer effect from Spanish pro-drop. The Spanish-English bilingual Dual-Path model can also produce code-switched sentences, even though it was never exposed to code switches during training (Tsoukala, Frank, Van den Bosch, Valdés Kroff, & Broersma, 2019). The patterns of generated code switches show some resemblance to those of Spanish-English bilinguals.…”
Section: Bilingual Rnn Sentence Productionmentioning
confidence: 98%
“…We have already seen that surprising phenomena can emerge when monolingual models are turned bilingual or when bilingual models become multilingual: The bilingual Dual-Path model displays unexpected transfer and code-switching behavior (Tsoukala et al, 2017(Tsoukala et al, , 2019, and RNN translation systems can translate between new language pairs (Johnson et al, 2017).…”
Section: Beyond Bilingualism: Is There Anything Special About Multilimentioning
confidence: 99%
“…We have already seen that surprising phenomena can emerge when monolingual models are turned bilingual, or when bilingual models become multilingual: The bilingual Dual-path model displays unexpected transfer and code-switching behaviour (Tsoukala et al, 2017(Tsoukala et al, , 2019 and RNN translation systems can translate between new language pairs (Johnson et al, 2017). As more languages are added, more opportunities for such emergence arise.…”
Section: Beyond Bilingualism: Is There Anything Special About Multilimentioning
confidence: 99%
“…First, we present a novel method of researching code-switched sentence production using computational cognitive modeling. To that end, we employ the Bilingual Dual-path model (Tsoukala et al, 2017) that can produce sentences in two languages, including code-switched ones. Second, using this method, we shed light on a production phenomenon that has been observed in the Spanish–English-speaking community in the US and is known as the “auxiliary phrase asymmetry” (Dussias, 2003; Guzzardo Tamargo et al, 2016; Lipski, 1978; Pfaff, 1979; Poplack, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we will showcase how we can use computational modeling to add and remove semantic weight from the Spanish auxiliary verb, thus investigating whether the asymmetry could be derived from the properties of Spanish and English. For that reason, we have employed the Bilingual Dual-path model (Tsoukala, Frank & Broersma, 2017), a connectionist model of bilingual sentence production that produces code-switches (see Section 3 for an explanation of the model).…”
Section: Introductionmentioning
confidence: 99%